Instagram in English Language Learning: A Systematic Literature Review - Awal Kurnia Putra Nasution (Asosiasi Dosen Perguruan Tinggi Islam, 2023)
In the ever-growing digital era, social media, especially Instagram, plays a significant role in English language learning. The platform is a multifaceted communication tool and offers visual and interactive features to enhance the student learning experience. This research analyzes the use of Instagram in the context of English language learning through a Systematic Literature Review (SLR) approach. The article selection process involved two stages: selection based on the title and abstract and selection based on the full text. An article search using the keywords